FORMATION OF ELITOLOGY OF CONSCIOUSNESS AND FACTORS AFFECTING IT (Academicia Globe: Inderscience Research, 2021)
The article deals with the dialectics of elite consciousness and social processes, the issues of the influence of elite upbringing on the formation of personality. The social difference between the elite and the masses is analyzed, first of all, as a special function of the elite consciousness, the theory of "spiritual perfection" is substantiated as a reflection of the elite consciousness. For the spiritual world of a person is determined by his elite consciousness. And the essence of Human Being is his ability to cognize the world. This means that knowledge and cognition are the main factors of elite consciousness.